Digital Learning Transformation: Game-Based Learning for Students’ Academic Motivation and Self-Efficacy - Andi Nadia Qarirah Rafifah Alisyahbana; Andi Ahmad Arif; Rizky Rahmawati Saudi; M. Ahkam Alwi (Jurusan Teknik Informatika dan Komputer, 2025)
Conventional learning methods often fail to ignite students’ internal drive to learn, particularly in subjects requiring abstract comprehension. This study examined the impact of game-based learning on students’ academic motivation and self-efficacy through a quasi-experimental pretest-posttest control group design. A total of 40 high school students aged 16–17 were selected based on low baseline scores in both variables. Participants were equally assigned to an experimental group (n=20), which received game-based instruction using the Quizizz platform in Economics lessons, and a control group (n=20), which continued with conventional teaching methods. Results revealed a substantial increase in academic motivation scores in the experimental group, from a pretest mean of 86.15 to a posttest mean of 129.05 (ΔM = 42.90, p < 0.001), while the control group showed a slight decline (ΔM = -1.55). Similarly, self-efficacy scores in the experimental group rose from 54.75 to 82.00 (ΔM = 27.25, p < 0.001), compared to minimal change in the control group (ΔM = -0.25). The intervention successfully elevated all students in the experimental group from “low” to “moderate” motivation and self-efficacy categories, with 10% reaching “high” motivation. These findings demonstrate that game-based learning, when designed with psychological engagement in mind, offers a powerful tool for fostering internal motivation and academic confidence. The study affirms the role of digital innovation not merely as a medium of delivery, but as a strategic approach to redesign learning experiences that are both effective and empowering.